Tax Competition Between Sub-Central Governments - Blöchliger, Hansjörg (OECD Publishing, 2011)
Tax competition is the strategic interaction of tax policy between sub-central governments (SCG) with the objective to attract and retain mobile tax bases. Tax competition rests on firms' and households' willingness and ability to shift the tax base - i.e. profits, capital, income, consumption etc. - after SCG tax policy changes. There is no tax competition without tax base mobility. The views on the benefits and costs of tax competition differ widely: while some consider that tax competition brings sub-central fiscal policy closer to citizen's preferences, increases the efficiency of the public sector and avoids tax and spending excesses, others argue that tax competition leads to a distorted tax structure, to growing tax rate disparities and to an under-provision of publicly provided services. The degree of tax competition is likely to vary across countries and over time and is strongly shaped by the fiscal and institutional framework. Tax competition is not only an issue for federal countries, but also for unitary countries where local governments often have far-reaching tax autonomy
Keywords: Taxation